PATTERN OF ANTIBIOTICS USE IN ADULT PATIENTS WITH URINARY TRACT INFECTION (UTI) - Hidayatul Kurniawati (Berkala Kedokteran, 2021)
Introduction: Urinary tract infection (UTI) is an infectious disease caused by the growth and proliferation of bacteria in the urinary tract, including infections in the bladder to the renal parenchyma with a certain number of bacteria in the urine. The use of antibiotics is therapy that commonly used to treat infectious diseases caused by bacteria. Irrational use of antibiotics can lead to bacterial resistance and toxicity. Objective: To determine the rationality of using antibiotics in adult patients with a urinary tract infection (UTI) in the X Hospital Yogyakarta from January-December 2017.Methods: This study is a non-experimental study with a descriptive observational study design and retrospective data collection. The sample of this study was inpatients with a diagnosis of urinary tract infection (UTI) and was recorded in the Medical Record X Hospital Yogyakarta for the period January-December 2017 which was included in the inclusion criteria. Results: Medical records that were included in the inclusion criteria were 61. The single most widely used antibiotic was ceftriaxone in 25 cases (44.64%) and the most widely used combination antibiotic was ceftazidime + levofloxacin in 2 cases (40%). The use of antibiotics with the right indication was 61 patients (100%), the right type was 61 patients (100%), the correct duration was 54 patients (88.52%), the right dose was 61 patients (100%), the right interval was 60 patients (98.36%) and the right route of administration was 61 patients (100%).